Solvency Ii Risk Management Requirements: A Spotlight On Algeria's Insurance Industry - Riad Meriem (جامعة الوادي University of Eloued, 2024)
This article provides a comprehensive examination of Solvency II objectives, focusing on provisioning methods in Property and Casualty insurance. It elucidates the three pivotal pillars of Solvency II and their profound impact on the insurance sector. The practical implementation of solvency regulations in Algerian insurance companies is scrutinized. The key findings reveal that the adoption of Solvency II in Algeria encounters multiple challenges, including structural, legislative, transformation-related, and governance and disclosure issues. To address these challenges, the adoption process requires impact studies, simulations, and tests, similar to the European market's practices.
Keywords: Solvency II; provisioning methods; insurance sector; Implementation; Challenges